AUTHORITY OF THE PROSECUTOR DURING INVESTIGATION (Bulletin of criminological association of Ukraine, 2023)
The powers of the prosecutor during the investigation were investigated due to their connection with his functional purpose. It is suggested that the main functions of the prosecutor in the criminal process as a whole and during the investigation include the following: public prosecution, procedural management and pre-trial investigation. Depending on the functional orientation, it is proposed to distinguish the following powers: 1) aimed at implementing the function of public prosecution; 2) those aimed at implementing the function of procedural management; and 3) aimed at implementing the pre-trial investigation function. It is also proposed to classify the powers of the prosecutor depending on the stage of inquiry into: 1) powers at the initial stage of inquiry; 2) authority at the stage of notifying a person of suspicion and selecting a preventive measure for a person; and 3) authority at the stage of completion of inquiry. It was determined that the powers of the prosecutor differ depending on the nature of his activity, which can be: 1) directed to the collection of evidence during the investigation (independently conducting procedural actions or giving orders to the investigator, operatives to carry them out, or the powers aimed at carrying out organizational tasks from coordination of inquiry). It is also proposed to classify the powers of the prosecutor during the inquiry according to their legal enshrinement: a) those defined in the Constitution of Ukraine; b) those specified in the Code of Criminal Procedure of Ukraine; c) those defined in the Law of Ukraine "On the Prosecutor's Office" and other laws of Ukraine, and d) those defined in secondary regulatory legal acts. The need to supplement Art. 36 of the Criminal Procedure Code of Ukraine by the provision on the prosecutor's exercise of powers to supervise compliance with the law when applying coercive measures related to the restriction of the personal freedom of citizens during inquiries and criminal proceedings in general.
Keywords: criminal proceedings; inquiry; public; prosecutor; functions; powers